Primerjava hoje s pripomočkom za hojo (Femuret) in hojo z nadkolensko protezo pri bolnikih po amputaciji zaradi bolezni žilja - Erjavec, Tatjana (Rehabilitacija (Ljubljana), 2013)
Background: The aim of the study was to establish if walking with the early walking device Femuret is more straining than walking with a transfemoral prosthesis with locked knee for patients with transfemoral amputation. Methods: Ten patients with transfemoral amputation because of vascular disease and comorbidity were included in the study. The oxygen consumption (VO2 ) with the direct method, heart frequency and ECG changes were measured during the 6-minute walking test. We also measured blood pressure before and after the test and the walked distance. The velocity of walking was calculated. The patients estimated their effort with Borgs scale. Walking efficiency with metabolic and physiological consumption index were estimated. Results: There were no statically significant differences in oxygen consumption, maximal heart frequency and blood pressure between walking with the Femuret and with a transfemoral prosthesis. Statistically significant differences were observed in walking distance and walking velocity (p<0,001). Oxygen consumption was on average 50% of the maximal predicted with respect to age, and maximal heart frequency about 70 % of the maximal predicted. Walking with a transfemoral prosthesis was more effective in terms of the metabolic and physiological consumption index than walking with the Femuret (p < 0.001). Conclusion: At an individually chosen speed, energy consumption is equal when walking with a transfemoral prosthesis or with the Femuret. Both constitute moderate physical acitivity. Because of higher speed, walking with a transfemoral prosthesis is more effective then walking with the Femuret.
Keywords: early walking devices; hoja; pripomočki za zgodnjo hojo; transfemoral amputation; transfemoralna amputacija; Walking